Influence of different fat replacers and drying techniques on physicochemical characteristics and sensory attributes of regular and instant reduced-fat coffee creamer - Hedayatnia, Simin (2015)
Coffee is one of the most popular soft drinks all around the world. Most of coffee drinkers prefer to add creamer and/or whitener to their coffee before sunsumption. Coffee creamers usually contains high amount of the saturated fat (15-40%). Therefore, the frequent consumption of the whitened coffee can induce many health issues (e.g. cardiovascular and chronic diseases) for coffee drinkers. In recent years, the demand for low- and reduced-fat products has been extensively increased. The aim of the present study was to formulate and characterize the reduced-fat coffee creamer with the most desirable characteristics comparable with commercial creamers. The main objective of the present study was to investigate the effects of different type and content of fat replacer (i.e. inulin, 0, 2.5, 5 and 7.5%; maltodextrin, 0, 15, 20 and 25%, w/w) as well as different drying techniques (i.e. spray drying, drum drying and fluidized-bed drying) on physicochemical properties, microstructures, and sensory attributes of the regular-and instant reduced-fat creamers. The regular coffee creamers were produced by a single-stage drying (either spray drying or drum drying only); while the instant reduced-fat coffee creamers were produced by a double-stage drying (i.e. spray drying or drum drying along with fluidized-bed drying). Physicochemical properties of all formulated creamers were compared with the control (as a negative control) and commercial creamers (as a positive control). The current study revealed that the physicochemical characteristics, microstructures, and sensory attributes of both regular-and instant reduced-fat creamers were significantly (p ≤ 0.05) influenced by both fat replacers and drying techniques. Moisture content, water activity of regular-and instant creamers were notably decreased by increasing the concentration of maltodextrin and inulin. This could be due to significant (p ≤ 0.05) increase in solid content of samples. The bulk density of regular-and instant creamers was dropped by increasing the content of target fat replacers and enlarging the particle size. The current study revealed that the wettability, solubility, viscosity and glass transition temperature of the formulated creamer were significantly (p ≤ 0.05) improved as the contents of inulin or maltodextrin in the creamer formulation were increased. The present study revealed that spray dried reduced-fat creamer had smaller spherical or oval shape particles than the drum dried creamers; while drum dried samples had much bigger particles with irregular shape. In this study, the drum-dried creamers had darker colour (or lower lightness) than the spray-dried samples. This might be because of its higher drying temperature and longer residence time. The drum-dried creamers with markedly bigger particle size and lower moisture content had considerably lower bulk density than the spray-dried creamer. The current study revealed that the instant reduced-fat creamer had higher glass transition temperature than the regular reduced-fat creamer. This could be explained by the fact that the instant reduced-fat creamer had markedly lower moisture content than the regular creamer because the application of fluidized-bed drying led to decrease the moisture content, water activity, bulk density and stickiness. The agglomeration induced by fluidized bed drying significantly increased the reconstitution properties (wattability and solubility), viscosity and glass transition temperature of the reduced fat creamer. The morphology analysis revealed that agglomeration caused by fluidized-bed drying resulted in bigger particles with more porous structure than the regular creamer. Finally, the current study revealed that the instant spray-dried creamer (containing 25% maltodextrin and 7.5% inulin) had better quality comparable with commercial creamer than the instant drum-dried sample with similar formulation. The current study showed that instant spray-and drum dried reduced-fat creamers containing high amounts of maltodextrin (25%, w/w) and inulin (7.5%, w/w) had the most desirable characteristics among all formulated creamers comparable with the commercial creamer.